The contribution of anthropogenic sources to the aerosols over East China Sea. (February 2016) - Wang, Fujiang; Chen, Ying; Meng, Xi; Fu, Jiangping; Wang, Bo
Abstract: Total suspended particulate (TSP) samples were collected at a pristine island (Huaniao) in northern East China Sea (ECS) between Mar. 2011 and Jan. 2013 and analyzed for the concentrations of major ions and trace elements. Aerosol sources and the distribution of source regions are identified using positive matrix factorization (PMF) and potential source contribution function (PSCF) methods. It is found that aerosols over Huaniao Island are contributed by six main factors including primary industrial emissions (11.3%), secondary aerosol (22%), oxalate-associated aerosol (15.7%), sea salt (36.7%), ship emission (6.3%) and mineral dust (8.1%). Anthropogenic source contribution to the resolved aerosol mass reached the highest (76.6%) and lowest (18%) values in January 2013 and August 2012 respectively, strongly influenced by the prevailing winds of East Asian monsoon. The main source regions of secondary aerosol are southeastern Hebei and Shandong, which is consistent with the most intensive distribution of coal-fired power plants and the largest emission of precursors in this area. Oxalate-associated aerosol is produced primarily along the coastal line. Primary industrial emissions mainly originate from southwestern Shandong and Yangtze River Delta. Highlights: Six main contributors to aerosols over coastal ECS are identified. Over 50% of resolved aerosol mass is contributed by anthropogenic sources. Anthropogenic emissions are mainly from Shandong and Yangtze River Delta. Ship emission is a significant source of aerosols over coastal ECS in summer.